Fluorometric Liposome Screen for Inhibitors of a Physiologically Important Bacterial Ion Channel - Fernandes, Andreia S.; Pombinho, António; Teixeira-Duarte, Celso M.; Morais-Cabral, João H.; Harley, Carol A. (Frontiers in Microbiology, 2021)
The bacterial K+ homeostasis machinery is widely conserved across bacterial species, and different from that in animals. Dysfunction in components of the machinery has an impact on intracellular turgor, membrane potential, adaptation to changes in both extracellular pH and osmolarity, and in virulence. Using a fluorescence-based liposome flux assay, we have performed a high-throughput screen to identify novel inhibitors of the KtrAB ion channel complex from B. subtilis, a component of the K+ homeostasis machinery that is also present in many bacterial pathogens. The screen identified 41 compounds that inhibited K+ flux and that clustered into eight chemical groups. Many of the identified inhibitors were found to target KtrAB with an in vitro potency in the low µM range. We investigated the mechanisms of inhibition and found that most molecules affected either the membrane component of the channel, KtrB alone or the full KtrAB complex without a preference for the functional conformation of the channel, thus broadening their inhibitory action. A urea derivative molecule that inhibited the membrane component of KtrAB affected cell viability in conditions in which KtrAB activity is essential. With this proof-of-concept study, we demonstrate that targeting components of the K+ homeostasis machinery has the potential as a new antibacterial strategy and that the fluorescence-based flux assay is a robust tool for screening chemical libraries.